Spatial Distribution of COVID-19 Related to the Potential for Spreading Outbreaks and Vulnerability of a Region in Bengkulu Province on 2020 - Naurah Shafa Putri Cahyangi; Dessy Triana; Liya Agustin Umar; Nikki Aldi Massardi; Utari Hartati Suryani; Riry Ambarsari (UNIB PRESS, 2022)
Coronavirus disease 2019 (COVID-19) was declared a pandemic on March 11, 2020, by the World Health Organization (WHO). The spread of COVID-19 increases with different conditions and situations in each region. Spatial distribution plays a role in identifying the vulnerability of an area. This study aimed to determine the differences in COVID-19 cases from one area to another in 10 regions in Bengkulu Province in 2020. This study is a descriptive study with an observational study through a cross-sectional approach using an epidemiological investigation form as a data source. Sampling was carried out from July to December 2020 and obtained from 3044 respondents who met the inclusion criteria. The total sampling technique did sampling. The relationship between the population density of an area and the severity of COVID-19 cases was statistically analyzed using the Spearman rank test. The results showed that areas with higher density levels, such as Bengkulu City, caused a wider spread of cases, causing the number of COVID-19 cases to increase compared to other areas with lower population densities in Bengkulu Province. There is no significant relationship between population density and the severity of COVID-19